Endogenous Enfranchisement When Groups’ Preferences Conflict - Conley, John P.; Temimi, Akram (Journal of Political Economy, 2001)
In their seminal paper, Aumann, Kurz, and Neyman found the surprising result that the choice of levels of public goods in a democracy is not affected by the distribution of voting rights. This implies that groups of individuals may not value the franchise. This conclusion, however, does not correspond to what we commonly observe. We propose a new model to address the question of enfranchisement. The main feature of our model is that it takes into account natural affinities, such as religion or class, that may exist between voters. This allows us to show that while individuals may not value the vote, they nonetheless value the franchise. We also show that in the presence of nonconvexities, it is more likely that the group in power will grant the franchise when preferences are severely opposed.